2004
DOI: 10.1128/iai.72.9.5298-5307.2004
|View full text |Cite
|
Sign up to set email alerts
|

A Salmonella fim Homologue in Citrobacter freundii Mediates Invasion In Vitro and Crossing of the Blood-Brain Barrier in the Rat Pup Model

Abstract: From the invasive Citrobacter freundii strain 3009, an invasion determinant was cloned, sequenced, and expressed. Sequence analysis of the determinant showed high homology with the fim determinant from Salmonella enterica serovar Typhimurium. The genes of the invasion determinant directed invasion of recombinant Escherichia coli K-12 strains into human epithelial cell lines of the bladder and gut as well as mannose-sensitive yeast agglutination and were termed fim Cf genes. Expression of the Fim Cf proteins wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Previous work in a mouse model of stroke has shown that HUCBC infusion results in significant reduction in the infarct volume as well as rescue of neurological deficits associated with decreased proinflammatory cytokine production [19]. Additionally, we previously found reduced parenchymal and vascular b-amyloid deposits in AD mouse model.…”
Section: Hucbc Infusion Improves Motor Skills and Spatial Working Memorymentioning
confidence: 93%
See 3 more Smart Citations
“…Previous work in a mouse model of stroke has shown that HUCBC infusion results in significant reduction in the infarct volume as well as rescue of neurological deficits associated with decreased proinflammatory cytokine production [19]. Additionally, we previously found reduced parenchymal and vascular b-amyloid deposits in AD mouse model.…”
Section: Hucbc Infusion Improves Motor Skills and Spatial Working Memorymentioning
confidence: 93%
“…Immunohistochemical staining was performed using mouse monoclonal anti-human Ab [17][18][19][20][21][22][23][24] antibody (clone 4G8; Covance Research Products, Emeryville, CA) or rat anti-mouse CD45 antibody (AbD serotec, Raleigh, NC) in conjunction with the VectaStain Elite ABC kit (Vector Laboratories, Burlingame, CA) coupled with diaminobenzidine substrate. For all the staining, a set of sections without adding primary antibody were used as negative staining control.…”
Section: Immunohistochemical Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The ␥ 1 -fimbrial clade corresponds to FUP cluster 1 (367) and consists of ushers present in several bacterial species, all belonging to a single family within the Gammaproteobacteria (the Enterobacteriaceae). Representatives are present in Citrobacter freundii (FimD) (133), E. coli (AufC, ECs0594, ECs2110, FimD, FmlC, FocD, SfaF, SfmD, YcbS, and YdeT) (17,33,45,56,73,128,177,202,203,271,274,297,340,352), Proteus mirabilis (AtfC) (213,214), and S. enterica serotype Typhimurium (BcfC and FimD) (218,337). A number of usher proteins are closely related to the ␥ 1 -fimbrial clade but are not connected by a node with a good bootstrapping value (Fig.…”
Section: The ␥-Fimbriaementioning
confidence: 99%